2013
DOI: 10.1097/tp.0b013e318295eeb7
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Lung Perfusion

Abstract: There is a critical mismatch between the number of donor lungs available and the demand for lungs for transplantation. This has created unacceptably high waiting-list mortality for lung transplant recipients. Currently (2012) in the United Kingdom, there are 216 patients on the lung transplant waiting list and 17 on heart and lung transplant list. The waiting times for suitable lungs average 412 days, with an increasing mortality and morbidity among the patients on the lung transplant list. Ex vivo lung perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Ex vivo lung perfusion (EVLP) may increase donor yield by monitoring and reconditioning extended-criteria donor lungs. 1,2 However, the safety of extended preservation with EVLP is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo lung perfusion (EVLP) may increase donor yield by monitoring and reconditioning extended-criteria donor lungs. 1,2 However, the safety of extended preservation with EVLP is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, injured lungs that require reconditioning may not be ready for transplant within this timeframe. 2 The current study evaluates three perfusates for 24H EVLP on OCS: RBCs without plasma, autologous whole donor blood, and acellular buffered dextran-albumin solution (BDAS). It demonstrates that the safe interval for extended preservation of swine lungs is longer than that currently in use for human lung transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach, kidney donors have been pre-treated with immunomodulatory drugs such as methotrexate, with mixed results on 5-year graft survival (3639). The emerging use of ex-vivo lung perfusion circuits, which can facilitate both mechanical and pharmacologic leukocyte depletion, may improve lung allograft survival by reducing the passenger leukocyte load; and recent studies have demonstrated successful removal of passenger leukocytes from human lung allografts (40,41). …”
Section: Discussionmentioning
confidence: 99%
“… 7 During this assessment period, organs can be resuscitated and potentially repaired if once deemed suboptimal for transplantation. Since there is a huge difference between the demand for organs for transplantation and the number of donor organs available, 8 increasing the number of donor organs available via ex vivo perfusion can go a long way in decreasing the transplantation waiting list mortality rates. The understanding of organ perfusion has only been possible by observing the potential effects of hypoxic injury on donated organs.…”
Section: General Mechanism For Preservation Of Ex Vivo Organ Systemsmentioning
confidence: 99%
“…Specifically, for SCS, the organs are then immersed in fresh sterile solutions, double-bagged, and buried in melting ice in transport containers. 8 …”
Section: General Mechanism For Preservation Of Ex Vivo Organ Systemsmentioning
confidence: 99%